Study on Pyrolysis Characteristics of Micro-emulsified Diesel Fuel. (2018) - Chen, Nan; Tao, Gang; Zhang, Li-jing
Abstract: In order to understand the effect of moisture on the pyrolysis process of micro-emulsified diesel fuel, the pyrolysis characteristics of micro-emulsified diesel fuel were analyzed by thermogravimetric analysis. Thermogravimetric experiments on micro-emulsified diesel fuel with various water contents (0%, 5%, 10%, 15%) and heating rates (10℃/min, 30℃/min, 50℃/min) were conducted. The results showed that the samples were evaporated slowly in the initial stage of the pyrolysis process. Then the water was evaporated and the pyrolysis was accelerated. In the later stage, the samples were pyrolyzed deeply and the loss of weight was greatest. The pyrolysis gradually stopped in the last stage. In addition, the loss of thermogravimetric weight for micro-emulsified diesel fuel tended to lower temperature area with the increasing of water content. Moisture can slow down the pyrolysis process of micro-emulsified diesel fuel. With the increasing of heating rate, the evaporation hysteresis occurred and the effect of pyrolysis was getting better.